ANALISIS AGROINDUSTRI NENAS UD BERKAT BERSAMA DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Mufti Mufti; Rini Nizar; Niken Nurwati (Jurnal Ilmiah Pertanian, 2017)
Pineapple (Ananas comosus L) is a fruit crop coming from Brazil. Besides pineapple can be eaten directly can be further processed into chips pineapple, pineapple dodol, jam, syrup and others. In the village there Nenas Kualu agro-industrial raw material, namely pineapple pineapple chips, diamonds pineapple and pineapple dodol. Pineapple chips are most widely refined products developed by craftsmen in the village Kualu pineapple processing pineapple. Processing of agricultural or agro-industry is a subsystem of agribusiness very big role in increasing the added value of agricultural products. Employers will also seek to do business with a decent order to obtain the maximum revenue to improve their welfare. In connection with this condition, this study aims to conduct feasibility analysis, Break Even Point (BEP), and the added value that can be produced by the pineapple industry. The results showed that the Agro-Industry Pineapple "Thanks to the Joint Enterprises in May 2016 to produce pineapple chips of 651 Kg. With a production cost of Rp. A sum of 45,475,122, - and the revenue generated Rp. 13,114,878, -. Results BEP analysis shows that this business in the breaks even when producing pineapple chips 60 kg with admission of Rp. 5,371,598, -. If the expected profit of Rp. 20.000.000, -, sales of chips should reach 902 Kg. the added value generated by effort "Berkat Bersama" is Rp. 872, - /kg of fresh pineapple.